2020
DOI: 10.21608/ejhc.2020.152563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Progressive Muscle Relaxation Technique on Post-Operative Pain and Quality of Recovery among Patients with Abdominal Surgeries

Abstract: Background: Abdominal surgery is considered one of the most painful surgical procedures as the site's proximity to the diaphragm and extensive cross-innervations in the area increasing the postoperative pain. Progressive Muscle Relaxation (PMR) is a promising intervention for these complains. Aim of the study was to determine the effectiveness of progressive muscle relaxation technique on post-operative pain and postoperative quality of recovery. Research design: A quasi experimental research design with a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, lower anxiety and pain, as well as higher stability of patients who were offered relaxation techniques, are in favor of this conclusion. Likewise, Elsayed et al (2020) in Egypt [ 44 ] found progressive muscle relaxation to be significantly effective in decreasing postoperative pain and improving the postoperative quality of patients' recovery after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, lower anxiety and pain, as well as higher stability of patients who were offered relaxation techniques, are in favor of this conclusion. Likewise, Elsayed et al (2020) in Egypt [ 44 ] found progressive muscle relaxation to be significantly effective in decreasing postoperative pain and improving the postoperative quality of patients' recovery after surgery.…”
Section: Discussionmentioning
confidence: 99%